(untitled) (International Journal of Functional Research in Arts and Humanities (IJFRAH), 2025)
Reading-induced anxiety, a pervasive yet understudied phenomenon, significantly impacts academic performance and psychological well-being among undergraduates. This study explores the prevalence, predictors, and implications of reading-induced anxiety on maladaptive test engagement among 400 undergraduates in Cross River State, Nigeria. Using a cross-sectional survey design, primary data were collected via the Reading-Induced Anxiety Scale (RIAS) and the Test Engagement Inventory (TEI). Findings reveal that 48.5% of participants experienced moderate to severe reading-induced anxiety, with females and younger students reporting higher levels. Academic level and faculty type showed no significant correlation with anxiety, but high anxiety levels were strongly associated with maladaptive test engagement behaviors, such as procrastination and avoidance (r = .62, p < .01). The Cognitive Interference Theory and Self-Regulation Model provided theoretical grounding, highlighting how anxiety disrupts cognitive resources and test preparation. Demographic factors, including gender and socioeconomic status, significantly predicted anxiety levels. The study underscores the need for targeted interventions, such as cognitive-behavioral strategies and reading support programs, to mitigate anxiety and enhance test engagement. Recommendations include integrating anxiety management workshops into university curricula and fostering supportive academic environments. Future research should explore longitudinal effects and cultural influences on reading-induced anxiety.